Klondikers in temporary camp building boats at Lake Lindeman, British Columbia, Chilkoot Trail, probably 1898 - Warner, Arthur Churchill, 1864-1943 (1898)
After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897.<vr> Caption on image: Arthur C. Warner. 319 On verso of image: Lake Linderman, Alaska. A.C. Warner, Photographer, Seattle, Wash., 707 12th Ave. Skaguay, Dyea, Chilkoot Pass. Warner 97 Filed in Alaska series.